2019
DOI: 10.1021/acs.analchem.9b04531
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Protein Precipitation for Drug Target Discovery on the Proteomic Scale

Abstract: High-throughput drug discovery is highly dependent on the targets available to accelerate the process of candidates screening. Traditional chemical proteomics approaches for the screening of drug targets usually require the immobilization/modification of the drug molecules to pull down the interacting proteins. Recently, energetics-based proteomics methods provide an alternative way to study drug–protein interaction by using complex cell lysate directly without any modification of the drugs. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 35 publications
0
73
0
Order By: Relevance
“…Although the proteome coverage is poor, there were still four kinases showing significant stabilization only in SIP but not in the initial staurosporine MS‐CETSA study which was performed in K562 cell extract, suggesting some extent of complementarity of the different approaches. However, we note these kinases could possibly exist in different forms in the different cell lines (293T vs. K562) 28,46 …”
Section: Differential Solubility‐based Target Deconvolution—sipmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the proteome coverage is poor, there were still four kinases showing significant stabilization only in SIP but not in the initial staurosporine MS‐CETSA study which was performed in K562 cell extract, suggesting some extent of complementarity of the different approaches. However, we note these kinases could possibly exist in different forms in the different cell lines (293T vs. K562) 28,46 …”
Section: Differential Solubility‐based Target Deconvolution—sipmentioning
confidence: 93%
“…Recently, Zhang et al 28 developed a new approach named SIP, which is based on the observation that compared to free proteins, ligand‐bound proteins are more tolerant to organic SIP. More specifically, the cell lysate aliquots in the presence and absence of ligand of interest are equilibrated with a series of concentrations of a mixed organic solvent (acetone/ethanol/acetic acid = 50:50:0.1) to initialize protein denaturation and precipitation.…”
Section: Differential Solubility‐based Target Deconvolution—sipmentioning
confidence: 99%
See 1 more Smart Citation
“…Various agents, including salt, acid, organic solvents, and some chemical denaturants, also disrupt protein folding leading to aggregation and precipitation (Chan et al, 1986; Meng et al, 2018; Shih et al, 1992; Wingfield, 1998). Recently, it was demonstrated that increasing concentrations of an organic solvent mixture composed of 50% acetone, 50% ethanol, and 0.1% acetic acid (AEA) induces precipitation of protein lysates and, more importantly, that this property can be exploited to identify ligand binding events (Zhang et al, 2020). This method, termed solvent-induced precipitation (SIP), provided the basic framework for a robust target engagement approach.…”
Section: Introductionmentioning
confidence: 99%
“…This property can be influenced by physical association with ligands and other molecules, making individual proteins more or less susceptible to solvent-induced denaturation. Herein, we report the development of proteome-wide solvent shift assays by combining the principles of solvent-induced precipitation (Zhang et al, 2020) with modern quantitative proteomics. Using this approach, we developed solvent proteome profiling (SPP), which is capable of establishing target engagement through analysis of SPP denaturation curves.…”
mentioning
confidence: 99%